PRINCIPAL LEADERSHIP AND TEACHER PERFORMANCE IN IMPROVING THE QUALITY OF SCHOOLS IN INDUSTRY 4.0 ERA - Hasibuan, Ahmad Tarmidzi; Lubis, Khoirun Nisa; Sihotang, Icha Peratiwi; Sibagariang, Munawwaroh (Darul Ilmi Bina Insan Foundation, 2023)
The advancement of educational quality has to align with the advancement of the nation's civilization as capitalization in the future. As we enter the industrial revolution, the quality of education must improve. However, in order to increase the quality of schools today, the principal's influence and the successes of educators are required, because the principal is the school's leader and has authority in the school. Appropriate leadership is the force that bridges the changing demands of Industry 4.0. every leader is required to keep abreast of technological developments so that they can lead, improve, control, direct, and motivate their members who participate in organizing and improving educational learning in the era of the industrial revolution 4.0. This study aims to identify the quality of school principals in their leadership and teacher performance when improving school quality according to changing times, especially in the 4.0 era. The design applied to this research is a qualitative method. The results of this discussion came to the conclusion that school principals and the performance of teachers must be able to use technology in schools because it is very much needed in the current era of the digital revolution 4.0, it is necessary to realize existing potential and improve and explore the need for readiness of school leaders to face the challenges of the digital revolution 4.0